Microbial consortium with multifunctional attributes for the plant growth of eggplant (Solanum melongena L.) - Kaur, Tanvir; Devi, Rubee; Negi, Rajeshwari; Kumar, Sanjeev; Singh, Sangram; Rustagi, Sarvesh; Shreaz, Sheikh; Rai, Ashutosh Kumar; Kour, Divjot; Yadav, Ajar Nath (Folia microbiologica, 2024)
In the past few decades, the pressure of higher food production to satisfy the demand of ever rising population has inevitably increased the use synthetic agrochemicals which have deterioration effects. Biostimulants containing beneficial microbes (single inoculants and microbial consortium) were found as an ideal substitute of synthetic chemical fertilizers. In recent years, microbial consortium is known as a better bioinoculant in comparison to single inoculant bioformulation because of multifarious plant growth-promoting advantages. Looking at the advantageous effect of consortium, in present investigation, different bacteria were isolated from rhizospheric soil and plant samples collected from the Himalayan mountains on the green slopes of the Shivaliks, Himachal Pradesh. The isolated bacteria were screened for nitrogen (N) fixation, phosphorus (P) solubilization and potassium (K) solubilization plant growth promoting attributes, and efficient strains were identified through 16S rRNA gene sequencing and BLASTn analysis. The bacteria showing a positive effect in NPK uptake were developed as bacterial consortium for the growth promotion of eggplant crop. A total of 188 rhizospheric and endophytic bacteria were sorted out, among which 13 were exhibiting nitrogenase activity, whereas 43 and 31 were exhibiting P and K solubilization traits, respectively. The selected three efficient and potential bacterial strains were identified using 16S rRNA gene sequencing as Enterobacter ludwigii EU-BEN-22 (N-fixer; 35.68 ± 00.9 nmol C2H4 per mg protein per h), Micrococcus indicus EU-BRP-6 (P-solubilizer; 201 ± 0.004 mg/L), and Pseudomonas gessardii EU-BRK-55 (K-solubilizer; 51.3 ± 1.7 mg/mL), and they were used to develop a bacterial consortium. The bacterial consortium evaluation on eggplant resulted in the improvement of growth (root/shoot length and biomass) and physiological parameters (chlorophyll, carotenoids, total soluble sugar, and phenolic content) of the plants with respect to single culture inoculation, chemical fertilizer, and untreated control. A bacterial consortium having potential to promote plant growth could be used as bioinoculant for horticulture crops growing in hilly regions.
Keywords: draslík; Nitrogen; Potassium; fosfor; Rhizosphere; RNA, Ribosomal, 16S; fixace dusíku; rhizosféra; Microbial Consortia; Nitrogen Fixation; půdní mikrobiologie; mikrobiální společenstva; Phylogeny; Plant Roots; Phosphorus; Bacteria; Plant Development; Soil Microbiology; Solanum melongena; vývoj rostlin; fylogeneze; kořeny rostlin; RNA ribozomální 16S; dusík